Characteristics of Quizizz-Based Reading Skill Assessment Tools in BIPA Learning 1 - Wahyu Mutiana; Ida Zulaeha; Rahayu Pristiwati (Universitas Negeri Semarang, 2025)
Technology is an important part in the context of BIPA learning. The demands of industry 5.0 provide positive opportunities for the quizizz application to be utilized in BIPA assessment. Therefore, the purpose of this study is to describe the characteristics of the needs of quizizz-based reading skill assessment devices in BIPA 1 learning. The data in this study are interview conversions and the percentage of learner and teacher needs for the product. The data sources in this study are learners and teachers from the BIPA Wisma Bahasa Yogyakarta program, BIPA Walisongo State Islamic University Semarang, and BIPA Sultan Agung Islamic University Semarang. Data analysis for this study was carried out using the needs data analysis technique. This study uses a mixed method as a methodological approach, and the theory of assessment devices is used as a theoretical approach. The findings of the researcher, namely the characteristics of the needs of quizizz-based reading skill assessment devices in BIPA 1 learning, include material aspects, construction aspects, language aspects, and quizizz application aspects. Characteristics of the material aspect, namely a) the principle of completeness, b) the principle of suitability, c) the principle of validity, d) the principle of integration, and e) the principle of sufficiency. Characteristics of the construction aspect include a) the principle of completeness, and b) the principle of systematicity. The characteristics of the language aspect include a) the principle of ease, and b) the principle of communication. The characteristics of the quizizz application consist of a) the principle of practicality, b) the principle of economy, and c) the principle of novelty.